Multiple regions of the transporter associated with antigen processing (TAP) contribute to its peptide binding site - Nijenhuis, Marga; Hämmerling, Günter J. (The journal of immunology, 1996)
The transporter associated with Ag processing (TAP) translocates cytosolic peptides into the endoplasmic reticulum, where they can bind to MHC class I molecules. TAP does not translocate all peptides with equal efficiency, but selects peptides with regard to both their length and their sequence and, in this manner, affects the pool of peptides available for binding to MHC class I molecules. It has been demonstrated that peptide selection by TAP predominantly occurs during the first step in the translocation process, namely the association of the peptide with a binding site present on the TAP molecule. In this study, we identify four regions, two on the TAP1 and two on the TAP2 subunit, that make major contributions to this binding site. For both TAP1 and TAP2, the identified regions overlap with the cytosol-membrane boundaries of the two transmembrane segments closest to the ATP binding site. Our data are consistent with a model in which the transmembrane segments of TAP form a pore in the membrane, with the peptide binding site being formed by the cytosolic mouth of this pore.